INSPIRED but Tired: How Medical Faculty’s Job Demands and Resources Lead to Engagement, Work-Life Conflict, and Burnout - Lee, Rebecca S.; Son Hing, Leanne S.; Gnanakumaran, Vishi; Weiss, Shelly K.; Lero, Donna S.; Hausdorf, Peter A.; Daneman, Denis (Frontiers in Psychology, 2021)
Background Past research shows that physicians experience high ill-being (i.e., work-life conflict, stress, burnout) but also high well-being (i.e., job satisfaction, engagement). Objective To shed light on how medical faculty’s experiences of their job demands and job resources might differentially affect their ill-being and their well-being with special attention to the role that the work-life interface plays in these processes. Methods Qualitative thematic analysis was used to analyze interviews from 30 medical faculty (19 women, 11 men, average tenure 13.36 years) at a top research hospital in Canada. Findings Medical faculty’s experiences of work-life conflict were severe. Faculty’s job demands had coalescing (i.e., interactive) effects on their stress, work-life conflict, and exhaustion. Although supportive job resources (e.g., coworker support) helped to mitigate the negative effects of job demands, stimulating job resources (e.g., challenging work) contributed to greater work-life conflict, stress, and exhaustion. Thus, for these medical faculty job resources play a dual-role for work-life conflict. Moreover, although faculty experienced high emotional exhaustion, they did not experience the other components of burnout (i.e., reduced self-efficacy, and depersonalization). Some faculty engaged in cognitive reappraisal strategies to mitigate their experiences of work-life conflict and its harmful consequences. Conclusion This study suggests that the precise nature and effects of job demands and job resources may be more complex than current research suggests. Hospital leadership should work to lessen unnecessary job demands, increase supportive job resources, recognize all aspects of job performance, and, given faculty’s high levels of work engagement, encourage a climate that fosters work-life balance.